2021
DOI: 10.2147/opth.s336356
|View full text |Cite
|
Sign up to set email alerts
|

A One Year Longitudinal Comparative Analysis of Visual Outcomes Between Femtosecond Laser-Assisted Cataract Surgery and Standard Phacoemulsification Cataract Surgery

Abstract: Purpose To assess visual outcomes over time of femtosecond laser-assisted cataract surgery compared to standard phacoemulsification cataract surgery. Design A retrospective, single-center comparative study. Methods Patient data including demographics, ocular biometry, pre- and postoperative visual acuity, postoperative complications, primary (uncorrected distance visual acuity over time) and secondary visual outcomes (uncorrected near visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…Our study showed the significant difference of internal SR between PHACO and L Astig -FLACS group ( P < 0.05). Other MTF and SR in each group did not show the significant difference, which is consistent with existing research findings [ 16 , 25 , 26 ]. SR and MTF is an useful parameter of optical quality, which is closely associated with aberrations [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed the significant difference of internal SR between PHACO and L Astig -FLACS group ( P < 0.05). Other MTF and SR in each group did not show the significant difference, which is consistent with existing research findings [ 16 , 25 , 26 ]. SR and MTF is an useful parameter of optical quality, which is closely associated with aberrations [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…The femtosecond laser automated the four initial manual steps performed in cataract surgery [ 15 ] to reduce the amount of energy required for PHACO. Although there are theoretical benefits to surrounding structures from reduced ultrasonic emulsion energy, there is still debate about the effectiveness of FLACS in this regard [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…FLACS involves using a femtosecond laser to assist in the initial steps of the cataract surgery, such as clear corneal incision, capsulotomy, and lens nucleus fragmentation. However, much debate remains on this topic, with studies even claiming that there is no difference in visual outcomes between both methods [3] . The Meta-analysis conducted by Chen et al [1] on 25 randomized controlled trials (RCTs) collected before November 2, 2019 compared parameters such as visual outcomes and complication rates between FLACS and CPCS.…”
Section: Dear Editormentioning
confidence: 99%
“…The only effective treatment known so far is to perform a cataract surgery. Currently, most of those interventions are performed using conventional methods, i.e., by means of phacoemulsification [2]. Cataract surgery is one of the most frequently performed surgeries worldwide.…”
Section: Introductionmentioning
confidence: 99%